The Littlest SRAM. - Savage, N. (IEEE spectrum)
A new type of lithography that uses an electron beam to spark a chemical reaction could provide a way to build incredibly tiny transistors, which the chipmaking industry will require in a few years. Researchers from Taiwan and the University of California, Berkeley, say they've made static RAM that anticipates 16-nanometer chip features using a new process called nanoinjection lithography.